Implikasi Kelangkaan Pupuk Bersubsidi Pada Produktivitas Hasil Panen Tanaman Padi Di Sokduwet, Kecamatan Pekalongan Selatan - Nurul Kharisma; Hendri Hermawan Adinugraha; M. Shulthoni (Strategic: Journal of Management Sciences, 2024)
Objective. The purpose of this study is to determine how farmers in Sokoduwet, South Pekalongan subdistrict, respond to the phenomenon of the scarcity of government-subsidized fertilizer and whether subsidized fertilizer has a relationship with rice productivity. Research Method. This research uses a qualitative method with a case study approach. Results. The study found that farmers not only complained about the scarcity of subsidized fertilizers but also that fertilizer prices continued to increase. This is not proportional to the results obtained by farmers during the harvest season. Several factors are causing the scarcity of government-subsidized fertilizers, including farmers' lack of awareness to register for e-RDKK. In addition, farmers do not immediately redeem subsidized fertilizers when encouraged to do so by using the Tani Card, so retailers can sell subsidized fertilizers to anyone, including farmers whose names are not registered in the government system. The phenomenon of subsidized fertilizer scarcity also has implications for farmers' behavior in dealing with this phenomenon. Among them are the wise use of subsidized fertilizers, the use of inorganic fertilizers balanced with organic fertilizers, and the hoarding of subsidized fertilizers by farmers as a form of preparedness when this phenomenon occurs again. Conclusion. Farmers in Sokoduwet, South Pekalongan Subdistrict, stated that rice productivity is not only based on the use of fertilizers, but other factors can affect crop productivity, such as high rainfall intensity during the harvest season.